PENGENALAN SENI ECOPRINT SEBAGAI MEDIA EDUKASI KREATIF DAN PELESTARIAN LINGKUNGAN BAGI SISWA SEKOLAH DASAR DI SD NEGERI TEMBULUN KELURAHAN MEKARSARI - Holilah, Futri Alaida; Mulani, Ratu Emillyan; Afriani, Raden Irna; Oktavitri, Yollanda; Rustandi, Tata; Munsiroh, Munsiroh; Meida, Dedeh (Yayasan Education and Social Center, 2025)
This study aims to introduce ecoprint art as a creative educational medium and a means of environmental conservation for elementary school students. The activity was carried out by students from Universitas Bina Bangsa at SD Negeri Tembulun, Kelurahan Mekarsari, through a series of stages including socialization, ecoprint technique demonstration, hands-on student practice, and reflection. This research employed a descriptive qualitative method, with data collected through observation, interviews, questionnaires, and documentation. The results showed that students were highly enthusiastic during the ecoprint-making process and were able to understand the connection between art and the environment. The activity not only enhanced students’ creativity but also fostered their awareness of utilizing natural materials and the importance of environmental preservation from an early age. In addition, the program received positive responses from teachers and the school, who expressed interest in continuing the initiative as a sustainable program. Thus, ecoprint has proven to be an effective contextual learning method that can be implemented in elementary education, particularly in instilling environmental values through an artistic approach